An Interview with Dr. Taylor Eighmy - Sarah Russell (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
The University of Tennessee welcomed Dr. Taylor Eighmy in October of 2012 as the new Vice Chancellor for Research and Engagement. Dr. Eighmy comes with many years of experience working to develop research initiatives, grants, and contracts for university research, having previously worked at Texas Tech University and the University of New Hampshire. In an interview on January 22, 2013, he discussed the importance of research at public universities, his personal experiences with research, and his goals for research development at the University of Tennessee.
Keywords: Taylor Eighmy; Undergraduate Research; University of Tennessee